The Influence of Organizational Commitment on Work Engagement with Inclusive Leadership as a Moderator - I Nyoman Aditya Bharatha Nada; I Gede Riana (CV. Adiba Aisha Amira, 2025)
This study investigates organizational commitment effect on work engagement, with inclusive leadership as a moderating variable. The central concern examined pertains to the limited level of employee engagement, especially prevalent bureaucratic public sector organizations. The research was conducted at the South Kuta District Office using an explanatory quantitative approach. Data were collected through questionnaires administered to 63 purposively selected respondents and analysis was performed using PLS-SEM with WarpPLS 7.0 software. The findings revealthat organizational commitment and inclusive leadershippartially have a significant effect on work engagement. However, the interaction between organizational commitment and inclusive leadership did not demonstrate a significant moderating effect, it suggest that inclusive leadership does not strengthen the influence oforganizational commitment on work engagement. These results imply that the two variables operate independently in influencing employee engagement. The practical implication of this study highlights the importance of fostering both organizational commitment and inclusive leadership practices to enhance work engagement. Future research is encouraged to investigate the potential mediating variables and to adopt a longitudinal approach to gain deeper insights.